Impaired immunity in patients with inflammatory bowel disease and hyposplenism: the response to intravenous phi X174. Issue 3 (March 1981) - Ryan, F P; Jones, J V; Wright, J K; Holdsworth, C D
Abstract : Eight patients with inflammatory bowel disease were tested for their ability to mount a serological response to the intravenous particulate antigen phi X174. Seven patients had extensive ulcerative colitis and one patient extensive Crohn's colitis, four having severe hyposplenism and four normal splenic function. The antibody response to phi X174 was grossly impaired in those with hyposplenism.